Brand Awareness and Market Development by Synergizing Customer Loyalty and CSR at Novotel Bali Benoa - I Gusti Ayu Nurtirtawaty; Ni Made Ernawati; I Gede Mudana; Putu Yunita Wacana Sari (International Journal of Travel, Hospitality and Events, 2024)
Purpose: This study intends to ascertain how much the Novotel Bali Benoa's brand awareness and market development are impacted by the synergy between its CSR and customer loyalty programs, as well as how the organization may best utilize these initiatives to maximize their impact. Research methods: The research methodology uses questionnaires and surveys to gather information from a number of respondents, including staff members and guests of hotels. Questionnaires, interviews, observations, document analyses, and focus group discussions are used to gather its data. Utilizing descriptive analysis, Smart PLS, and validity and reliability testing, quantitative analysis approaches are used to the data. Results and discussion: The study's primary conclusions show that Novotel Bali Benoa's brand awareness and market development are significantly boosted by the synergy between the customer loyalty program and CSR, which is founded on human- and nature-based principles and is implemented through digital marketing media. Customer loyalty may be generated by an efficient loyalty program, and consumers' perceptions of a brand are positively impacted by human-based and natural CSR. Implication: By optimizing digital marketing channels, bolstering brand recognition in the face of competition, enabling quick market expansion, and cultivating conscientious and encouraging new consumer loyalty, these two strategies work in concert to accomplish sustainable tourism.   Keywords: Brand awareness, customer loyalty, CSR.